The Relationship between Parenting Patterns and the Smoking Behavior of Adolescent Boys in MTs, Secang District: Hubungan Pola Asuh Orang Tua dengan Perilaku Merokok Remaja Laki-laki di MTs Kecamatan Secang - Saumaningrum, Melda; Mareta, Reni; Sulistyono, Dwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Background: Smoking behavior among adolescents in Magelang Regency has increased significantly. Many people say that Junior High School (JHS) youth are more often seen in groups and smoke with their friends after school. This has also been confirmed by the school. At JHS Secang Subdistrict, many of them were students from outside the area who moved for one reason or another, such as their parents' jobs. Schools have followed up on smoking cases at school, but many parents pay little attention to their children's behavior and some even allow their children to smoke. Purpose: To determine whether there is a relationship between parenting style and smoking behavior of adolescent boys in JHS Secang District. Methods: The research method uses a correlational quantitative descriptive method to test whether there is a relationship between parenting styles and smoking behavior. Results: The majority of respondents were light smokers with a total of 66 of 98 students (67.3%) and the parenting style used was authoritarian parenting with a total of 45 students (45.9%). Based on the Spearman statistical test, the results obtained were p value = 0.001. This shows that there is a relationship between parenting style and smoking behavior in young boys at Secang District JHS with the strength of the relationship or the correlation coefficient of 2 variables, namely parenting style and smoking behavior has a moderate relationship (0.320). Conclusion: There is a relationship between parenting style and smoking behavior of male teenagers at JHS Secang District.